2020
DOI: 10.1101/2020.01.29.911883
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cyclin E1 protein is stabilized inBRCA1mutated breast cancers leading to synergy between CDK2 and PARP inhibitors

Abstract: 26Basal-like breast cancers (BLBC) are aggressive breast cancers that respond poorly 27 to targeted therapies and chemotherapies. In order to define therapeutically 28 targetable subsets of BLBC we examined two markers: cyclin E1 and BRCA1 loss. 29 In high grade serous ovarian cancer (HGSOC) these markers are mutually exclusive, 30 and define therapeutic subsets. We tested the same hypothesis for BLBC. 31Using a BLBC cohort enriched for BRCA1 loss, we identified convergence between 32 BRCA1 loss and high c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 49 publications
2
11
0
Order By: Relevance
“…The association between cyclin E gene amplification and BRCA1/2 mutations have been examined previously and in studies with high grade serous ovarian cancer, such associations were found to be mutually exclusive [ 58 , 59 ]. However, when correlating cyclin E protein levels to BRCA1/2 mutations, studies in both ovarian and breast cancer patients show a significant level of correlation [ 60 , 61 , 62 ]. While mechanisms of regulation between BRCA1/2 and cyclin E remain unclear, a recent study suggested that BRCA1 mutation may stabilize cyclin E1 protein by decreasing phosphorylation T62 on cyclin E1 [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between cyclin E gene amplification and BRCA1/2 mutations have been examined previously and in studies with high grade serous ovarian cancer, such associations were found to be mutually exclusive [ 58 , 59 ]. However, when correlating cyclin E protein levels to BRCA1/2 mutations, studies in both ovarian and breast cancer patients show a significant level of correlation [ 60 , 61 , 62 ]. While mechanisms of regulation between BRCA1/2 and cyclin E remain unclear, a recent study suggested that BRCA1 mutation may stabilize cyclin E1 protein by decreasing phosphorylation T62 on cyclin E1 [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, when correlating cyclin E protein levels to BRCA1/2 mutations, studies in both ovarian and breast cancer patients show a significant level of correlation [ 60 , 61 , 62 ]. While mechanisms of regulation between BRCA1/2 and cyclin E remain unclear, a recent study suggested that BRCA1 mutation may stabilize cyclin E1 protein by decreasing phosphorylation T62 on cyclin E1 [ 62 ]. Phosphorylation T62 of full-length cyclin E1 [ 63 ], but not its LMWE forms, leads to its proteasome mediated degradation in the nucleus by FBWX7 [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…We explored the relationship between cyclin E1 protein expression and survival in BLBC by quantifying cyclin E1 expression across the kConFab familial breast cancer cohort [7]. Cyclin E1 expression was significantly higher in BLBC compared to non‐BLBC cases ( p < 0.0001) (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Molecular and clinical data were obtained for breast cancer patients from the Kathleen Cunningham Foundation Consortium for research into Familial Breast cancer (kConFab), as described in Ref. [7], and for HGSOC from the Australian Ovarian Cancer Study (AOCS), as described in Ref. [8].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation